Presence of Aspartate Aminotransferase in Peri-Implant Crevicular Fluid with and without Mucositis - Priyanka Devadiya; Yashika Goyal; Divya Divya; Jyoti Wasti; Dipooja Patil; Anamika Sinha; Mahesh Ghadage (Journal of Pharmacy and Bioallied Sciences)
Background: Aspartate aminotransferase (AST) is an enzyme commonly found in various body fluids and tissues, including peri-implant crevicular fluid (PICF). Its presence and activity in PICF have been implicated in inflammatory conditions such as mucositis around dental implants. Materials and Methods: This study aimed to compare the levels of AST in PICF collected from sites with mucositis (group A) and healthy sites (group B). PICF samples were collected using standardized paper strips and analyzed using enzymatic assays. The AST levels were quantified using a spectrophotometric method, and the data were statistically analyzed using Student’s t-test. Results: The mean AST level in group A (mucositis) was found to be 12.3 ± 2.1 U/mL, whereas in group B (healthy sites), it was significantly lower at 5.7 ± 1.3 U/mL (P < 0.05). These findings indicate a significant elevation of AST in PICF associated with mucositis compared to healthy peri-implant sites. Conclusion: Elevated levels of AST in PICF suggest its potential as a biomarker for detecting inflammatory conditions such as mucositis around dental implants. Monitoring AST levels in PICF could aid in the early detection and management of peri-implant diseases, contributing to improved clinical outcomes and implant longevity.